Ultrasound-Guided de Quervain's Tendon Release, Feasibility, and First Outcomes - Croutzet, Pierre; Guinand, Regis; Mares, Olivier; Apard, Thomas; Candelier, Gilles; David, Isabelle (Journal of Wrist Surgery, 2019)
Background de Quervain's syndrome is one of the main tendonitis of the wrist. The hypothesis of authors was that de Quervain's syndrome could be successfully treated with a specific ultrasound-guided percutaneous procedure, as it is for trigger finger.Surgical Technique Identification of the subcompartmentalization of the first extensor compartment was performed first, using the Hiranuma's classification, prior to the surgery. Then, we assessed precisely the positions of the sensory branches of the radial nerve and drew the landmarks. Through a continuous ultrasound in-plane control, we performed a percutaneous retrograde section of each part of the first compartment of the extensors, using a dedicated surgical blade.Methods In a cadaveric study, authors proposed to assess the feasibility and safety of a new and specific procedure and then assessed their first clinical cases. Fourteen specimen wrists were analyzed with ultrasound and the procedure was performed prior to an open control of the efficiency of the release, and safety for the superficial nerves. Then, we reported the results of the 22 first patients included in the clinical series.Results In a cadaver laboratory, authors were able to identify with ultrasound the type of first compartment septation (subcompartmentalization) in 13 cases (n = 14). The misidentification induced one incomplete release. No damages of the superficial radial nerve were observed despite close relationship. In the small series (n = 22), the duration of surgery was 8 minutes (range: 4–18 minutes). It was performed in office surgery and no morbidities were noticed. All patients improved, from quickDASH preoperative score of 59 (range: 28–71) to quichDASH postoperative score of 9 (range: 0–25).Conclusion Ultrasound-guided percutaneous release in the de Quervain's disease is a safe and reliable procedure without specific morbidity. Great care should be taken to avoid sensory nerve injuries and to identify the correct type of subcompartmentalization with a precise ultrasound evaluation.
Keywords: ultrasound surgery; de Quervain's disease; percutaneous